Prison Overcrowding: Alternative Sentencing in Indonesia’s Draft Criminal Code and Its Consequences on Correctional System - Nadia Utami Larasati; Fahlesa Munabari; Untung Sumarwan (Faculty of law Udayana University, 2022)
Imprisonment is often the most preferred choice of punishment in the eyes of law enforcement officers. As a result, prison overcrowding is inevitable and leads to the emergence of various problems in prisons. The discourse of alternative sentencing has recently gained increasing prominence in the Indonesian public with a view to addressing such problems amid the ongoing review of the Draft Criminal Code (Rancangan Kitab Undang-Undang Hukum Pidana/ RKUHP). This article aims to analyze alternative sentencing in the form of community service and probation penalties. It discusses the role and strategic measures taken by the Indonesian correctional system related to the performance of community correctional counselors in order to prepare for the implementation of alternative sentencing in the future. Employing a qualitative method, this study shows that alternative sentencing is principally in line with the concept of social reintegration and the philosophy of the current Indonesian Correctional Institution (Lembaga Pemasyarakatan). The correctional system in the country has also begun to take strategic measures to respond to the future implementation of the alternative sentencing in the RKUHP by means of updating the legal framework and improving infrastructure as well as the quality of human resources in accordance with the framework of community-based corrections.